Quality of life after liver transplantation with old donor graft - Flor, Maria José Nascimento (2016)
Objective: to compare the quality of life of liver transplant patients who received liver from donor aged ≤60 or >60 years old. Methods: a prospective study with a sample of 141 recipients from liver donors aged equal to or less than 60 years and recipients of elderly donor liver, in a reference center. Authors used a tool for identification and the Short Form-36. The Student-t and Mann-Whitney tests were applied for comparison between groups. Results: there were higher levels of quality of life with a statistically significant difference: Group A in social aspect (p=0.02) and Group B >50 months of transplantation (p=0.05) in physical component summary. Conclusion: the quality of life of liver receptors from older donor livers was similar to those who received a graft from younger donors in most dimensions. Transplanting time had a positive impact on the quality of life of elderly recipients.